EFEKTIVITAS MOBILISASI DINI DALAM PEMULIHAN LUKA PASIEN POST OPERASI SECTIO CAESAREA DI RUANG FLAMBOYAN RUMAH SAKIT IBU KARTINI KISARAN - Sri Legawati; Nurnelam Nasution (Jurnal Riset Hesti Medan, 2017)
Sectio caesarea is surgical operation for giving birth an embryo by opening abdominal wall and uterus wall. However, we need to remember that another having surgery is someone need a carefull supervision relating with the dangerous ruptura uteri. The purpose of this research is to identify early mobilization effective illustration to help the discovering of patients’ injured after sectio caesarea surgery in flamboyan room Ibu Kartini hospital KisaranThe research design is descriptive by using observasional research by using accidental. The populations in this research are patients coming while doing post sectio caesarea observation in ibu kartini hospital kisaran. By using accidental sample in order to get respondents for 20 mothers.Based on the result of the research from early mobilization effective in discovering on the injured of caesarea sectio operation post patient get the result 13,55 (90,33 %). So the conclusion is a good mother in doing eraly mobilization. The conclusion is a mother has a good category in doing early mobilization in discovering the operation injured.